STRATEGI GURU SD DALAM MENGINTEGRASIKAN NILAI-NILAI KARAKTER PADA PEMBELAJARAN TEMATIK - Vika Nadiana; Des Sinta Sari; Muhammad Roihan Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the strategies used by elementary school teachers in integrating character values into thematic learning. Character values such as responsibility, honesty, cooperation, and tolerance are essential components of the national education goals and must be instilled early through the learning process. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews, classroom observations, and documentation of learning tools. The research subjects were second and fifth-grade teachers at SD Negeri 5 Metro Pusat who have consistently implemented the 2013 Curriculum. The results show that the strategy for integrating character values is carried out in three main stages: (1) learning planning that explicitly includes character values in the lesson plan (RPP), (2) learning implementation that combines explicit and implicit approaches through habituation, teacher role-modelling, and collaborative thematic activities, and (3) character evaluation conducted through reflection, attitude observation, and anecdotal records. This study concludes that the success of character value integration is strongly influenced by the teacher’s awareness, the active role of students, and the support of the school environment. These findings are expected to serve as a reference for the ongoing development of character education practices in elementary schools.